Genomic substrates of neurophysiological endophenotypes: Where we've been and where we're going. (December 2014) - Braff, David L.
Abstract This special issue of Psychophysiology is focused on an imaginative and labor‐intensive examination of the genomic substrates of heritable neurophysiological endophenotypes in the Minnesota Center for Twin and Family Research (MCTFR) cohorts. The authors artfully combine the power of family‐based behavioral data with the atheoretical genome‐wide association study (GWAS) platform to enrich the examination of the genomic substrates of endophenotypes. Neurophysiological endophenotype deficits are found in psychiatric patients and are heritable in families of these psychiatric patients, allowing the investigators to combine the explanatory power of endophenotypes, with their known neural and functional substrates, with the otherwise agnostic identification of genes in the GWAS platform. This amplifies the power of the MCTFR endophenotype database. These well‐considered studies add significantly to our understanding of normal human neurobiology and stimulate the use of these endophenotypes to expand our knowledge of the role of these measures and their genomic substrates in normal and psychopathology research.